2020
DOI: 10.1021/acsami.0c12541
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mechanism of High Structural Stability of Nickel-Rich Cathode Materials by Adjusting Li-Excess

Abstract: It has been a long-term challenge to improve the phase stability of Ni-rich LiNi x Mn y Co 1−x−y O 2 (x ≥ 0.6) transition metal (TM) oxides for large-scale applications. Herein, a new structure engineering strategy is utilized to optimize the structural arrangement of Li 1+x (Ni 0.88 Mn 0.06 Co 0.06 ) 1−x O 2 (NMC88) with a different Li-excess content. It was found that structure stability and particle sizes can be tuned with suitable Li-excess contents. NMC88 with an actual Li-excess of 2.7% (x = 0.027, Li/TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 67 publications
1
72
0
Order By: Relevance
“…Chu and co‐workers recently investigated the influence of the Li‐excess during calcination on the Li/TM mixing. [ 35 ] The schematic diagram shown in Figure 6 a shows that the samples prepared with Li/TM ratios of 1.00, 1.06, and 1.12 are denoted by E00, E06, and E12, respectively. It is found that the Li slab in the lattice will experience shrinkage under both Li‐loss (E00) and Li‐excess (E12) conditions.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chu and co‐workers recently investigated the influence of the Li‐excess during calcination on the Li/TM mixing. [ 35 ] The schematic diagram shown in Figure 6 a shows that the samples prepared with Li/TM ratios of 1.00, 1.06, and 1.12 are denoted by E00, E06, and E12, respectively. It is found that the Li slab in the lattice will experience shrinkage under both Li‐loss (E00) and Li‐excess (E12) conditions.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…a) Reproduced with permission. [ 35 ] Copyright 2020, American Chemical Society. b) Reproduced with permission.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…1 However, as a single power source, LIB requires it to be able to store and release higher energy, which puts forward higher requirements for the energy density of battery materials, especially cathode materials. [2][3][4][5][6] Since "high voltage" cathode materials is an effective way to improve the energy density of batteries, the development of high voltage cathode materials with higher cost performance is a hot spot in the research of lithium ion batteries. [7][8][9] As far as the current research is concerned, the main research direction is LiMnNiO 4 (4.8 V) of spinel structure and LiMnPO 4 (4.1 V), LiCoPO 4 (4.8 V) and LiLiPO 4 (5.2 V) of olivine structure.…”
Section: Introductionmentioning
confidence: 99%
“…At present, lithium‐ion battery (LIB) is considered as the most potential power battery, which has been widely used in mobile electronic products, power vehicles and energy storage devices 1 . However, as a single power source, LIB requires it to be able to store and release higher energy, which puts forward higher requirements for the energy density of battery materials, especially cathode materials 2‐6 . Since “high voltage” cathode materials is an effective way to improve the energy density of batteries, the development of high voltage cathode materials with higher cost performance is a hot spot in the research of lithium ion batteries 7‐9 …”
Section: Introductionmentioning
confidence: 99%
“…With the development of industry and economy of human society, environmental and energy problems have been becoming more and more serious. Developing a new energy of environmental protection and pollution-free and achieving greater energy efficiency are the important means to solve this problem (Liu Z. X. et al, 2016;Qi et al, 2019;Yu Z. L. et al, 2019;Zhu et al, 2019a,b). Supercapacitor as an environmentally friendly energy storage device has been demonstrated to be superior to traditional capacitors and rechargeable batteries, due to the high power density, fast storage and release energy rate, and long cycle stability (Xie et al, 2016(Xie et al, , 2018Hossain et al, 2017;Zhang Z. T. et al, 2017;Yao et al, 2018;Wei et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%